PSGL-1 Immune Checkpoint Inhibition for CD4+ T Cell Cancer Immunotherapy - DeRogatis, Julia M.; Viramontes, Karla M.; Neubert, Emily N.; Tinoco, Roberto (Frontiers in Immunology, 2021)
Immune checkpoint inhibition targeting T cells has shown tremendous promise in the treatment of many cancer types and are now standard therapies for patients. While standard therapies have focused on PD-1 and CTLA-4 blockade, additional immune checkpoints have shown promise in promoting anti-tumor immunity. PSGL-1, primarily known for its role in cellular migration, has also been shown to function as a negative regulator of CD4+ T cells in numerous disease settings including cancer. PSGL-1 is highly expressed on T cells and can engage numerous ligands that impact signaling pathways, which may modulate CD4+ T cell differentiation and function. PSGL-1 engagement in the tumor microenvironment may promote CD4+ T cell exhaustion pathways that favor tumor growth. Here we highlight that blocking the PSGL-1 pathway on CD4+ T cells may represent a new cancer therapy approach to eradicate tumors.